Religious Societies: Methodist and Evangelical 1738–1800 - Walsh, John (Studies in church history, 1986)
One does not have to believe in free trade to recognize that in religion as well as economic life the erosion of a monopoly can provoke an uprush of private enterprise. It must be more than coincidental that two modern ‘church in danger’ crises which accompanied an erosion of Anglican hegemony - the Revolution of 1688 and the constitutional crises of 1828-32 - were followed by bursts of voluntary activity. Clusters of private societies were formed to fill up part of the space vacated by the state, as it withdrew itself further from active support of the establishment. After the Toleration Act perceptive churchmen felt even more acutely the realities of religious pluralism and competition. Anglicanism was now approaching what looked uncomfortably like a market situation; needing to be promoted; actively sold. Despite the political and social advantages still enjoyed by the Church, the confessional state in its plenitude of power had gone, and Anglican pre-eminence had to be preserved by other means. One means was through voluntary societies. The Society for the Reformation of Manners hoped by private prosecutions to exert some of the social controls once more properly exercised by the Church courts. The S.P.G. sought to encourage Anglican piety in the plantations and the S.P.C.K. to extend it at home by promoting charity schools and disseminating godly tracts. It was a task of voluntarism to reassert, as far as possible, what authority remained to a church which, because it could not effectively coerce, had to persuade.